BIOACCUMULATION AND TOXICITY EVALUATION OF CADMIUM AND MERCURY IN LLANERO GRASS (Brachiaria dictyoneura) - ARROYAVE Q., Catalina; ARAQUE M, Pedronel; PELAEZ J., Carlos A. (Vitae, 2010)
The transfer of mercury and cadmium in Brachiaria dictyoneura was studied in terms of bioaccumulative capacity and as a bioindicator. During the evaluation cadmium in B. dictyoneura show a decrease of 65%. The toxicity of cadmium was correlated with the consecutive accumulation of the cation during the monitoring time. With respect to mercury, a decrease in cation content in the plant was observed 30 days after exposure, presenting possible phytoreductión of mercury ion Hg2+ to Hg° in B. dictyoneura and subsequent evaporation. The tolerance and accumulator capacity of B. dictyoneura could be used for phytoremediation of sites co-contaminated with Cd and Hg.